TRIAGE COMPETENCY AND ITS ASSOCIATED FACTORS AMONG HEALTHCARE PROVIDERS IN EMERGENCY DEPARTMENT IN KENYA - Faith Sabwa; Prof Ltd Col (Rtd) John Martin Okoth; Dr. Tecla Psuma Sum (Nurse and Health: Jurnal Keperawatan, 2023)
Background: In developing world triage is underutilized and often an ineffective area of health system. In Kenya triage system is considered under developed and there is no National acceptable Accident and Emergency (A&E) triage system. Objective: The main objective of the study was to assess triage competency and its associated factors among healthcare providers in emergency department at selected hospitals in Kakamega County. Methods: This was a cross-sectional study design. Census sampling was used to select the General Practitioner hospitals. Systematic sampling was used to select study participants from the 11selected hospitals. The study participants were 183 health care providers including; doctors, clinical officers and nurses working within the selected hospitals in accident and emergency departments. Data was collected using an observation check list and structured questionnaire. Data was analyzed using statistical package of social science software version 24. Inferential statistics were used to test the strength of association. Results: The triage competency skills observed were; Rapid assessment; high level of skills observed at a mean of 88.9, patient categorization; the skills were moderate at a mean of 79.1, and Patient allocation skills which was moderate at a mean of 79.2. Conclusion: The hospital should organize unit base training on triaging, formulate guidelines triaging, avail resources needed and supervise triage area.